Analisis Rasio Profitabilitas Dan Likuiditas Untuk Menilai Kinerja Keuangan Perusahaan (Studi Kasus Pada Perusahaan Sub Sektor Itobacco Manufacture Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019) - Andrianto, Beny; Suhada, Bambang (Jurnal Manajemen DIVERSIFIKASI, 2022)
Analysis of the company's financial statements is basically a calculation of ratios to assess the company's financial condition in the past, present, and possibly in the future. By analyzing the company's financial statements, it can be seen the financial position and performance of a company and whether the company has succeeded in achieving its goals. Tobacco manufacturing sub-sector companies or tobacco industry are shares of companies whose business units sell cigarettes in the community. The Ministry of Industry noted that the total workforce absorbed by the cigarette industry was 5.98 million people, consisting of 4.28 million workers in the manufacturing and distribution sector, and the remaining 1.7 million working in the plantation sector. Based on the level of profitability of PT H.M. Sampoerna Tbk is the company with the best performance compared to other tobacco manufacturing sub-sector companies. Based on the level of liquidity during the 2017-1019 period in terms of the current ratio, the overall tobacco manufacturing sub-sector companies have good financial performance. This is because the average current ratio produced is already above the industry standard average. Based on the quick ratio of PT H.M. Sampoerna Tbk and PT Wismilak Inti Makmur are the companies with the best financial performances because they have a quick ratio that is already above the industry standard average. Meanwhile, PT Gudang Garam Tbk and PT Bentoel Internasional Investama Tbk are companies with poor financial performance because they have a quick ratio that is still below the industry standard average. Keywords: Financial Performance, Liquidity, Profitability.